2016
DOI: 10.1007/s00604-016-1747-1
|View full text |Cite
|
Sign up to set email alerts
|

Turn-on fluorometric β-carotene assay based on competitive host-guest interaction between rhodamine 6G and β-carotene with a graphene oxide functionalized with a β-cyclodextrin-modified polyethyleneimine

Abstract: The authors describe a "turn-on" fluorometric method for determination of β-carotene. It is based on competitive host-guest interaction between rhodamine 6G (R6G) and β-carotene and graphene oxide nanoparticles that were functionalized with β-cyclodextrin (β-CD)-modified polyethylenimine (β-CD-PEI-GO). On addition of R6G to a solution of β-CD-PEI-GO, its fluorescence is quenched because of the inclusion of R6G into the β-CD moiety. Both Förster resonance energy transfer and electron transfer are likely to occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Nonemissive PEI was treated with hydroquinone at different concentrations at 60 °C for 90 min. Hyperbranched PEI, a dendritic polymer, contains abundant active amine groups on both the backbone and branch chains . It has previously been found that phenolic compounds in an alkaline solution are easily oxidized by ambient O 2 . Hydroquinone was oxidized to p -benzoquinone when PEI was added to the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Nonemissive PEI was treated with hydroquinone at different concentrations at 60 °C for 90 min. Hyperbranched PEI, a dendritic polymer, contains abundant active amine groups on both the backbone and branch chains . It has previously been found that phenolic compounds in an alkaline solution are easily oxidized by ambient O 2 . Hydroquinone was oxidized to p -benzoquinone when PEI was added to the solution.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the potential of targeted nanocarriers for chemical delivery to the plant vasculature, we used a model fluorescent chemical cargo, rhodamine 6G (R6G), that can be loaded in β‐cyclodextrins and delivered by nanocarriers ( Figure a). The quenching response of R6G caused by the reaction with β‐cyclodextrin through electron transfer, [ 99 ] indicates loading of R6G into these molecular baskets (Figure 5b). As the concentration of β‐cyclodextrin increases, the R6G fluorescence intensity decreases up to 0.02 µM concentration where there is a saturation of chemical cargo loaded on β‐cyclodextrins (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…The higher signal dispersion that was observed when using 2-HP-β-CD is likely due to strong binding between the dyes and 2-HP-β-CD as well as the high flexibility and water solubility of 2-HP-β-CD compared to the other hosts investigated . High binding constants between the alcohol analytes and cyclodextrin hosts increase the strength of interactions between the analyte, host, and dye, resulting in more sensitive analyte-induced signal changes, whereas greater flexibility and water solubility increase the availability of this host to participate in the desired interactions. Of note, control experiments conducted in the absence of cyclodextrin resulted in markedly lower dispersion of the signals with significant misclassification of the analytes observed.…”
Section: Resultsmentioning
confidence: 99%